Interaction of a new antiviral and antitumor photosensitizer hypericin with human serum albumin: molecular modeling study. (2002) - Hritz, Jozef; Ulicny, Jozef; Miskovsky, Pavol
Abstract : Molecular modeling has been employed to study the interaction of hypericin (Hyp) with human serum albumin (HSA). The structural model for Hyp/HSA complex is presented. Our results indicate that Hyp is bound in II A subdomain of HSA close to the tryptophan 214 (Trp214) (distance 5.12 Å between the centers of masses). In the presented model the carbonyl group of Hyp is hydrogen bonded to the Asn458. Another two candidates for hydrogen bonds have been identified between the bay-region hydroxyl group of Hyp and the carbonyl group of the Trp214 peptidic link and between the peri-region hydroxyl group of Hyp and Asn458 carbonyl group.